A confidence interval comparison chart to assess the sensitivity of acetylcholinesterase from Hemibagrus nemurus as a source of enzyme for insecticides detection - Asri, Nurul Aida Muhamad; Begum, Ghousia; Ahmad, Siti Aqlima; Yasid, Nur Adeela; Shukor, Mohd Yunus (Journal of Environmental Microbiology and Toxicology, 2017)
In this work, the potential of acetylcholinesterase (AChE) from Hemibagrus nemurus (Baung) as a sensitive tool to detect the presence of insecticides was assessed. The affinity partially purified fraction was utilized as a source of AChE for in vitro assay of the effect of insecticides on the AChE. The resultant IC50 values were then compared with published results. An IC50 confidence interval comparison chart coined Shukor’s chart was utilized to compare the sensitivity of the AChE from H. nemurus to various other published results. In this chart, the IC50 confidence interval (95%) values for a particular insecticide is placed at one end of the chart and lined up with published values of IC50. Two lines are then made crossing the entire chart and represent the 95% confidence interval value for H. nemurus. Any confidence interval values for targeted insecticides from published results that do not touch these two lines are deemed significantly different (p<0.05), either more or less sensitive judging whether they fall below or above the two lines, respectively, whilst any confidence interval values that fall in or touch the two lines are deemed comparable in sensitivity.The results show that the AChE from H. nemurus is more sensitive to diazinonoxon and comparable in sensitivity compared to commercial and other local fish sources suggesting that the ACHE from H. nemurus can be a cheaper alternative for the current commercially and locally available AChEs.